Hot gas cleaning : particle removal & desulphurisation - Abdullah, Luqman Chuah; Ismail, Mohd Halim Shah (Universiti Putra Malaysia Press, 2010)
This book brings together both theory and current process engineering especially in chemical process industries. It is aimed primarily for science and engineering students as well as environmentalists and practicing professionals with responsibilities or an interest in the gas cleaning field. It also provides the appropriate process information with emissions and control data, in which the potential for process fine-tuning is improved for both the flue gas emission control objectives. Apart from pollutant control, this book also provides the formation of the pollutants, which often offers the key abatement methods as an alternative to control methods. The overall motivation of this book is to cover flue gases from combustion as well as fuel gases from gasification processes, using various types of furnaces and boilers.